Parental Autonomy Support and Psychological Well-Being in Tibetan and Han Emerging Adults: A Serial Multiple Mediation Model - Lan, Xiaoyu; Ma, Chunhua; Radin, Rendy (Frontiers in Psychology, 2019)
A growing body of research has explored well-being in diverse cultural contexts, and indicates that the definition and perception of well-being vary according to cultural context. Little is known, however, about whether intercultural differences in China (i.e., Tibetan and Han) lead to different perceptions of well-being and how social contexts and personal characteristics are associated with well-being in Tibetan and Han emerging adults. Using a self-determination framework, the current study examines the relationship between parental autonomy support (PAS) and psychological well-being (PWB) in Tibetan and Han emerging adults in China. Guided by implicit theory and self-regulatory theory, we propose a serial multiple mediation model of growth mindset and grit in the association between PAS and PWB. Propensity score matching was used to balance the two ethnic groups in terms of age, gender, socioeconomic status (SES), with a ratio of one to two. Finally, 59 Tibetan (71.2% girls) and 118 Han (69.5% girls) emerging adults aged from 18 to 25 years were included in the current study, and completed an online questionnaire survey. Findings suggest that (a) Tibetan emerging adults perceived higher levels of PWB than their peers from the Han ethnic group; (b) a serial multiple mediation model for the association between PAS and PWB was supported in Han emerging adults; (c) the indirect effects between PAS and PWB varied between Tibetan and Han emerging adults. Our findings suggest that PAS and grit contribute to PWB of emerging adults in both cultural contexts, whereas growth mindset may be beneficial for Han emerging adults only.